Register-Based Subject Omission in English and its Implication for the Syntax of Adjuncts - Liliane Haegeman (Anglophonia)
The empirical focus of the paper is the register specific subject omission in English as manifested most saliently in the abbreviated written registers represented prototypically by diary writing. After providing a descriptive survey of the distributional restrictions of subject omission in the relevant register, the focus is on the argument/adjunct asymmetry in the relevant pattern: while subject omission is incompatible with fronted arguments in sentence-initial position, it remains fully compatible with what at first sight appear to be sentence-initial adjuncts in the same position. The paper develops a formal syntactic analysis of the position of adjuncts in English in the spirit of recent work in generative grammar, notably the cartographic framework, without, though, adopting all the formalisms of that framework. It is proposed that the observed argument/adjunct asymmetry observed in relation to subject omission comes about due to the fact that what at first sight appear to be sentence-initial adjuncts are in fact inserted in a structural position below the canonical subject position which hosts the deleted subject. For the development of this analysis the paper introduces an articulated subject field with a specialised subject position, thus adopting the view that the predicational relation is the core property of sentence structure. Observed restrictions on referential dependencies between the (omitted) subject of the matrix clause and a nominal contained inside an adjunct can also be captured by the analysis.